2010
DOI: 10.1515/epoly.2010.10.1.1446
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of polystyrene melts dissolved with supercritical nitrogen fluid during microcellular injection moulding

Abstract: There are several benefits of using the supercritical fluid microcellular injection moulding process. The part weight, melt temperature, viscosity, moulding pressure, shrink/warpage, and cooling/cycle time are all significantly reduced. The purpose of this study is to investigate the rheological behaviour of PS melt dissolved SCF of nitrogen during Microcellular Injection Moulding process applied with Gas Counter Pressure (GCP) technology. The application of gas into the mould cavity prior to the melt filling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Polymers and Fillers Molded Part Thickness, mm [4,7,8,11,13,16,22,23] PP GF20; PP/LDPE blends; PP + GF + Talc; PP-TPU; PP CF20; PP CF30; PP + EPDM + TALC 2.4-4.0 [6,9,15,17] PA66 GF 30 1.5-4.0 [7,24] PLA/PHBV; PLA/PTFE (fibril) 3.3-4.0 [10,12] PC; PC/ABS 1.7-4.0 [14,25] PS 3.0…”
Section: Entry In the Literature Listmentioning
confidence: 99%
“…Polymers and Fillers Molded Part Thickness, mm [4,7,8,11,13,16,22,23] PP GF20; PP/LDPE blends; PP + GF + Talc; PP-TPU; PP CF20; PP CF30; PP + EPDM + TALC 2.4-4.0 [6,9,15,17] PA66 GF 30 1.5-4.0 [7,24] PLA/PHBV; PLA/PTFE (fibril) 3.3-4.0 [10,12] PC; PC/ABS 1.7-4.0 [14,25] PS 3.0…”
Section: Entry In the Literature Listmentioning
confidence: 99%
“…Foaming after melting filling plays a significant role in packing function leading to shrinkage reduction, warpage minimization, and elimination of sink marks, etc. The process characteristics and molded part properties have been studied earlier [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Despite its advantage, MuCell also faces technology challenges that hinder its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic mold temperature control [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] uses cavity surface coating or film-insert mold surface to delay the heat transfer on the cavity surface leading to an elevated mold temperature during the melt-filling stage. An alternate and effective way of solving the surface quality issue is the use of counter-pressure techniques, particularly the gas counter-pressure (GCP) technology [ 20 , 21 , 22 , 23 , 24 ], that have been reported to effectively improve the part surface roughness. Bledzki et al [ 21 ] first reported a reduction in the part surface roughness (Rz) from 23 lm to 0.85 lm.…”
Section: Introductionmentioning
confidence: 99%
“…To produce foam cores by injection moulding, blowing agents are used, which are typically divided into physical blowing agents (PBAs) and chemical blowing agents (CBAs) [24–26]. PBAs such as CO 2 [27] or N 2 [28] are usually used in microcellular injection moulding technologies such as MuCell ® . PBAs are introduced into the plasticizing unit of the injection moulding machine in a supercritical state.…”
Section: Introductionmentioning
confidence: 99%